Green Sustainable Entrepreneurship Based on Blockchain Financial Practices - Vasiliki A. Basdekidou (Archives of Current Research International, 2018)
Today, the state-of-the-art research in entrepreneurship involves the application of both the disrupting distributed ledger technology and the innovative Blockchain data structure to finance, economy and management disciplines (i.e. corporate finance, peer-to-peer management, digital marketing, etc.). Despite the well known recognition of the importance and the role of the peer-to-peer computing in the development of entrepreneurial financial strategies, as well as distributed firms and decentralised companies, there have been just a few attempts to apply distributed Blockchain methodology to financial practices and a number of hot-red issues have arisen in this field. The purpose of this article is to indicate opportunities for useful applications in the developing field of green sustainable entrepreneurship research. Hence, this article introduces, describes, evaluates, and documents new sustainable Blockchain functionalities and corporate finance practices for green entrepreneurship.